The effect of multimodal nutrition intervention on glucose and lipid parameters of Arfa Iron and Steel Company workers - Peyman Sarsangi; Sahand NikAsa; Jaber Ganji; Hossein Fallahzadeh; Azadeh Nadjarzadeh (BMC Nutrition)
Abstract Objective This study investigated the impact of nutritional interventions on glycemic and lipid profile factors among workers. Design & participants This prospective before-after study was conducted on 1097 employees of Arfa Iron and Steel Company, Yazd, Iran. Setting At baseline, anthropometric indices, and laboratory parameters including lipid profiles, liver enzymes, glucose factors, and blood pressure were measured for all participants. Intervention A six-month multimodal nutrition intervention program was implemented, including nutritional education, healthier factory menu options, healthy cooking method education, and nutritional counseling. Main outcome measures After the six-month intervention, all initial anthropometric indices and laboratory parameters, (lipid profiles, liver enzymes, fasting blood glucose, and blood pressure) were reassessed. Results After six months, mean weight (2.5%), BMI (2.5%), total cholesterol (11.9%), LDL cholesterol (18.5%), triglycerides (0.5%), systolic and diastolic blood pressure (2.6%) significantly decreased, while mean HDL cholesterol increased (17%) (p < 0.001). However, fasting blood sugar and liver enzymes showed no significant change. Conclusions and implications The findings demonstrate that a multimodal nutrition intervention significantly improved anthropometric indices and lipid profiles among Arfa Iron and Steel Company workers. Such interventions could be considered for other factories to enhance worker health and potentially boost productivity. Trial registration The trial is registered retrospectively at the US National Institutes of Health (ClinicalTrials.gov). The registration in the US National Institutes of Health was done in 23/10/2024 with the registration number: NCT06654362.